An Approach to the Analysis of Vocational Education and Training Requirements - Kodama, Fumio (Management Science, 1970)
Systematic approaches to the problems of education and training are difficult because so many social and psychological variables are involved. As education and training can be viewed as a system, system analysis can be applied. Therefore, in this study, the education and training system is formalized in the form of a matrix which shows the relationship between curriculum and the behavior of the skilled worker who is adequately educated and trained. Based on the matrix, the optimal time allocation in the curriculum was solved. Crane work in the Japanese steel industry was selected as the subject of the study and the procedures by which the formalization can be applied to a practical problem were developed.